Consensus document of the Italian Association of Medical Oncology and the Italian Society of Palliative Care on early palliative care. Issue 2 (April 2019) - Corsi, Domenico C.; Turriziani, Adriana; Cavanna, Luigi; Morino, Piero; Ribecco, Angela S.; Ciaparrone, Marco; Lanzetta, Gaetano; Pinto, Carmine; Zagonel, Vittorina
A consensus document on early palliative care was produced by a committed Working Group of the Italian Society of Medical Oncology and the Italian Society of Palliative Care to improve the early integration of palliative care in medical oncology and to stimulate and guide the choices of those who daily face the problems of advanced stage cancer patients. The simultaneous administration of antineoplastic treatments and early palliative care was shown to be beneficial in metastatic cancer pathway outcomes. Patients who could benefit from early palliative care are those with an advanced cancer at presentation, a compromised PS for cancer, and/or morbidities, and who are too frail to receive treatment. According to the Bruera practice models, in which the combination of cancer management with early palliative care can be offered, three groups of patients needing simultaneous care were identified and three different models of the delivery of palliative care were proposed. In patients with good prognosis and low need of simultaneous care, the solo practice model and the request for consultations were suggested, while in patients with poor prognosis disease with high need of simultaneous care and in conditions with high need of simultaneous care, regardless of cancer prognosis, the integrated care approach should be offered. Palliative care consultation services are seldom accessible in the majority of Italian hospitals; thus the application of various practice models depends on available resources, and a shared care model with the structures of palliative care operating in the area is often required.